Intrinsic Motivation and Local Tax Compliance: An Exploratory Study in the Hospitality Sector - Aviandi Okta Maulana; Blasius Erik Sibarani (Universitas Ahmad Dahlan, 2026)
This study identifies the intrinsic drivers of local tax compliance in the Indonesian hospitality sector, especially in Yogyakarta, and explores how business actors’ perceptions and experiences influence the optimization of regional tax revenue. Using a convergent mixed-methods design, the research employed a five-point Likert-scale survey with open-ended items administered to 31 personnel responsible for tax matters through purposive snowball sampling. The quantitative data were analyzed descriptively, while the qualitative responses were examined thematically. The study reports a consistently high level of intrinsic motivation among hospitality taxpayers, with item means ranging from 4.39 to 4.45. It suggests that the respondents perceived tax compliance as a meaningful contribution to social welfare and regional development. The qualitative findings indicate that intrinsic motivation grounded in ethical responsibility is a key predictor of timely tax payments and accurate reporting. Perceived regulatory fairness, constructive responses from tax authorities, adequate taxpayer knowledge, and clear government communication all enhance both capacity and willingness to comply. Incentives and penalties also play a role in reinforcing compliant behavior. This study provides a valuable reference point for understanding intrinsic motivation in local tax compliance. The study contributes to the literature by applying CET to Indonesia’s self-assessment system. It offers new insights into the psychological drivers of compliance in local tax environments. The research highlights how intrinsic motivation contributes to tax compliance through constructive interaction between taxpayers and the government.